All-American murder : the rise and fall of Aaron Hernandez, the superstar whose life ended on murderers' row - Patterson, James, 1947-; Abramovich, Alex, 1972-; Harvkey, Mike (New York : Little Brown and Company, 2018)
Everyone thought they knew Aaron Hernandez. He was an NFL star who made the game of football look easy. Until he became the prime suspect in a gruesome murder. But who was Aaron Hernandez, really? All-American Murder will reveal the unvarnished truth behind the troubled star, with first-person accounts and untold stories--from his hometown of Bristol, CT to his college days in Gainesville, FL to the Patriots' NFL locker room where he ascended to stardom, to the prison where Hernandez spent his final days.
Keywords: Hernandez, Aaron; Hernandez, Aaron -- Trials, litigation, etc; Murder -- Massachusetts -- Case studies; Trials (Murder) -- Massachusetts -- Case studies; Football players -- Biography